The Negotiation of First Agreements under the Canada Labour Code - Solomon, Norman (Relations industrielles / Industrial Relations, 1985)
The purpose of this study is to analyse bargaining units which achieved first agreements and those that did not achieve first agreements in terms of: data relating to their Canada Labour Relations Board (CLRB) certification experience; data relating to basic bargaining unit characteristics; and in terms of data relating to the negotiation of first agreements.